Pengaruh Penggunaan Media Pembelajaran Interaktif terhadap Motivasi Belajar Siswa Sekolah Dasar - Sri Rahayu, Heni; Tatat Luswati, Neng (Papanda Publisher, 2022)
This study aims to explore the influence of interactive learning media usage on student learning motivation at SDN Silihwangi I. The research method employed quantitative analysis by collecting data through questionnaires distributed to the classes at SDN Silihwangi I. The analysis results indicate a significant positive relationship between the usage of interactive learning media and student learning motivation. This finding confirms that the more frequently interactive learning media are used in the learning process, the higher the level of student learning motivation. Additionally, qualitative analysis also reveals student responses, teacher perceptions, and classroom interaction dynamics towards the implementation of interactive learning media. The implications of these findings underscore the importance of integrating interactive learning media into elementary education curricula as a strategy to enhance student interest and participation in the learning process. This research contributes to our understanding of the effectiveness of interactive learning media in enhancing student learning motivation at the elementary school level and paves the way for the development of more dynamic and responsive learning approaches to meet student needs in the current era of information technology.